(untitled) (Bulletin of Kharkiv National University of Internal Affairs, 2020)
The article is focused on studying peculiarities of employment contracts with seasonal and temporary employees in Ukraine. The employment contract as the basis of the origin of labor relations with seasonal and temporary employees has been researched. The norms of the decrees of the Presidium of the Supreme Rada of the USSR “On working conditions of temporary employees and officials” dated from September 24, 1974 No. 311-09 and “On working conditions of employees and officials engaged in seasonal work” dated from September 24, 1974 No. 310-09 have been analyzed . It has been noted that peculiarities of legal regulation of employment contracts with temporary and seasonal employees relate primarily to their conclusion and termination, as well as content. It has been proved that some provisions of regulatory acts that regulate the employment of temporary and seasonal employees are outdated; others require some revision. It has been offered to develop modern regulatory acts on the application of temporary and seasonal work. These acts must first of all establish the concept: “seasonal employees – individuals hired under an employment contract for work that as a result of natural and climatic conditions performed not through a year, but during a certain period (season), not exceeding six months”; “temporary employees – individuals hired under an employment contract for a period up to two months, and for the replacement of temporarily absent employees, who retain their place of work (position) – up to four months”. It has been substantiated that the List of Seasonal Works and Seasonal Industries needs to be updated, based on the realities of the present day.